Exploring the optimal grazing intensity in desert steppe based on soil nematode community and function. (27th May 2022) - Gao, Zhiwei; Han, Chaowei; Huang, Jing; Liu, Ziying; Zhang, Li; Zhang, Guogang; Jia, Meiqing; Li, Xiaodan
Abstract: Grazing is a key regulator of the biodiversity of the desert steppe in Inner Mongolia and has important ecological significance for the sustainable development of underground ecosystems. In a 14‐year grazing intensity experiment, we systematically explored the changes in soil nematode communities in desert steppe soils and comprehensively evaluated the optimal grazing intensity for the sustainability of the desert steppe underground ecosystem. Using high‐throughput sequencing, we analyzed the soil nematode communities and their relationships with environmental factors. The 14‐year grazing experiment revealed a significant impact on the diversity and composition of the soil nematode community in the surface layer (0–10 cm) and on the soil nematode community in the whole soil layer (0–20 cm). Based on LEfSe multilevel discriminant analysis, we found that the relative abundances of Acrobeles, Cephalobus, Filenchus, Aphelenchus, Longidorella, Amplimerlinius, Aporcelaimellus, Acrobeloides, Dorylaimellus, Hemicycliophora, Thonus, Alaimus, and Oxydirus changed significantly under different grazing treatments. Considering the number and function of soil nematode communities, long‐term light grazing was found to significantly promote an increase in soil nematode diversity and helped maintain soil nematode community stability. We determined that the most suitable grazing intensity for the sustainability of the soil underground ecosystem of the desert steppe in Inner Mongolia is light grazing (0.91 sheep hm ‐2 0.5 yr ‐1 ). We have, thus, provided a tool for determining and evaluating optimal grazing intensities for sustainable soil underground ecosystems.